Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/87565641.2010.549875
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correlates of Children's Responsiveness to Intervention

Abstract: Functional imaging research has yielded evidence of changes in poor readers after instructional intervention. Although it is well established that within the group of children with poor reading there are differences in behavioral response to intervention, little is know about the functional correlates of responsiveness. Therefore, we acquired functional magnetic resonance imaging (MRI) data from children identified as “at risk for reading disability” who responded differently to a reading intervention (5 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…The findings from this study replicated those of previous studies reporting differences between children who respond adequately (AR) and inadequately (IR) to a reading intervention and typically developing (TD) children using MEG (Simos et al, 2002, 2005, 2007) and fMRI (Alyward et al, 2003; Davis, et al, 2011; Meyler et al, 2008; Odegard, et al, 2008; Shaywitz et al, 2004; Temple et al, 2003). In this study, we found group differences in the amplitude of the first positive peak (P1), where TD children generated larger amplitudes compared to AR over the right hemisphere, while AR showed larger amplitudes than IR over the left hemisphere.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings from this study replicated those of previous studies reporting differences between children who respond adequately (AR) and inadequately (IR) to a reading intervention and typically developing (TD) children using MEG (Simos et al, 2002, 2005, 2007) and fMRI (Alyward et al, 2003; Davis, et al, 2011; Meyler et al, 2008; Odegard, et al, 2008; Shaywitz et al, 2004; Temple et al, 2003). In this study, we found group differences in the amplitude of the first positive peak (P1), where TD children generated larger amplitudes compared to AR over the right hemisphere, while AR showed larger amplitudes than IR over the left hemisphere.…”
Section: Discussionsupporting
confidence: 85%
“…Additional differences were found in the right inferior frontal gyrus, where AR showed more activation than both IR and TD children. Davis et al (2011) also identified differences between AR and IR and TD children ( N = 16, 7.5 years) using fMRI and a letter-sound matching task. Differences among all three groups were found in the left superior temporal gyrus, while differences between the TD children and AR were found in the left angular gyrus.…”
Section: Neural Correlates Of Adequate and Inadequate Responsementioning
confidence: 91%
“…Consequently, participants varied substantially in literacy profiles, with some continuing to exhibit deficient reading and spelling, whereas others had apparently remediated reading difficulties and, in some cases, spelling deficiencies as well. To investigate the cortical signatures of this well-documented heterogeneity in dyslexia outcomes [27]–[28], we subdivided participants with a previous diagnosis of dyslexia into three groups: (a) children with current literacy deficits (no remediation), (b) children who remediated their reading deficits (partial remediation), and (c) children who remediated both reading and spelling deficits (full remediation).…”
Section: Introductionmentioning
confidence: 99%
“…Odegard and colleagues (2008) conducted a post intervention comparison of a small number of adequate and inadequate responders and found increased fMRI activation in the left inferior parietal region for responders to the reading intervention. Davis et al (2011) used fMRI to compare five adequate and five inadequate responders to a reading intervention. Responders showed increased activation of the left hemisphere posterior superior temporal and middle temporal gyri.…”
mentioning
confidence: 99%